Níveis de glicerina para novilhas mestiças criadas a pasto : desempenho animal e comportamento ingestivo - Farias, Mariana de Souza (2011)
The objective was to study the effect of including different levels of glycerin on animal performance, feed efficiency, digestibility and ingestive behavior of Heifers on Brachiaria brizantha cv Marandu. The experimental period was 102 days, being the first 14 days as an adaptation period of heifers to experimental diets and management. There were used 36 crossbred heifers with an average initial weight of 226 kg and 13 months old, distributed in a completely randomized design with four treatments and nine replications: G0.0 = control, G2.80 = 2.80%, G6.10 = 6.10 and G9.00 = 9.00% of glycerin in dry matter of the ingest diet. The crude glycerin had 16% methanol and for its elimination it was heated to 75 °C before mixing the concentrate. Heifers were weighed every 28 days for evaluation of average daily gain (ADG). The dry matter intake was estimated from fecal output, recorded with the aid of chromic oxide (Cr2O3) as an external marker and indigestible dry matter (DMi) as an internal marker. Apparent digestibility was estimated from fecal output determined by chromic oxide. Feeding behavior was conducted by monitoring the activities of the animals by means of continuous observations with annotations by 24 hours at every five minutes, the average number of chews per bolus rumen, the time spent ruminating each bolus and the number of bolus ruminated over the period was recorded using digital stopwatches being nine values per animal. The inclusion of glycerin in the diet of heifers determined a reduction (P <0.05) on the final end (PVF) and on the average daily gain (ADG) of heifers supplemented with Brachiaria brizantha cv. Marandu. The dry matter daily intake (kg / day) of the supplement, pasture and total was similar (P> 0.05) among treatments. The intake of ether extract increased linearly (P <0.05) as there was an increase of glycerol in diet (? = 61.995 + 0.975 x). Carbohydrate intake decreased linearly (P <0.05) depending on the levels of glycerol to diets. The inclusion of glycerol had no effect (P> 0.05) on the digestibility of dry matter, organic matter, neutral detergent fiber, protein, fat, carbohydrates and non-fibrous carbohydrates. Moreover, the inclusion of glycerin in the diets increased linearly (P <0.05) the digestibility of ether extract. The glycerin inclusion in heifer diet determined reduction (P <0.05) in the grazing time, a linear increase (P <0.05) in idle time, quadratic effect (P <0.05) in eating time and had no effect on rumination time. Therefore it did not affect (P> 0.05) the number of periods in grazing and rumination. However, the number of idle period showed a quadratic equation (P <0.05). The eating period showed a linear decrease (P <0.05) with increased levels of glycerin. The glycerin was not affected (P> 0.05) by the time period of grazing and rumination. The time of idle periods increased (P <0.05) linearly with increasing glycerin. The time had a quadratic effect (P <0.05). Feeding time and total chewing showed a linear decrease (P <0.05) with increased levels of glycerin. The glycerin had a varied effect on these variables, but do not significantly disturb the feeding behavior of heifers. In addition, the lower performance of Heifers can be attributed to the quality of glycerin and not by a change on the behavior.